Analysis of the Effect of Participatory Leadership Style on Employee Work Motivation at PT. BRI Syariah KC. Banjarmasin - Nurhayati Nurhayati; Maya Rezeki Angriani; Dewi Aina (J-MAS (Jurnal Manajemen dan Sains), 2022)
The analytical test used in this study is a simple linear regression analysis. The sample used is all employees of PT. BRI Syariah KC. Banjarmasin with a total sample of 85 people. Data were collected through answers from respondents to questions in the form of questionnaires distributed to respondents, namely employees of PT. BRI Syariah KC. Banjarmasin. The research hypotheses were tested by simple linear regression which met the test of classical assumption. The analysis results shows that the style of participatory leadership variable has a positive significant effect on employee loyalty (Y) PT. BRI Syariah KC. Banjarmasin, because the value of tcount (13.203) > ttable (2.006) and Ha is accepted. The simple linear regression equation obtained from the results of hypothesis testing is Y= 13.978 + 1.715X. From the regression equation, it can be seen that the participative leadership style is in line with work motivation. This is because the regression coefficient of each of these variables is positive, meaning that if the participatory leadership style experiences an increase, work motivation will also increase.